Molecular discrimination of Ancistrus lineages (Siluriformes: Loricariidae) using barcode DNA tool - de Borba, Rafael Splendore [UNESP]; Mariotto, Sandra; Centofante, Liano; Henrique Zawadzki, Claudio; Pasquali Parise-Maltempi, Patricia [UNESP] (Taylor & Francis, 2019)
Although several species of Ancistrus have been described from the Amazon and Paraguay river basins in the states of Amazonas and Mato Grosso, Brazil, the taxonomic status of most specimens from these regions remains doubtful. In the present work, cytogenetic and molecular data were used to discriminate and isolate unexpected Ancistrus lineages from the Amazon and Paraguay basins. For that, it was used DNA barcoding based on mitochondrial Cytochrome Oxidase Subunit I (COI) gene and cytogenic data to perform such molecular discrimination. The analyzed sequences had 669 bp, of which 171 bp were conserved and 491 bp were variable. The Neighbor-joining and Bayesian analysis revealed 21 distinct groups in topology. The genetic distances within each group was 0.4%, 21 times smaller than the mean distance observed among groups, which was 8.4%. These values showed seven distinct lineages of Ancistrus from the studied points of the Amazon basin and eight lineages from the Paraguay basin points. Our results illustrate the efficiency of this technique for the discrimination of the Ancistrus lineages once it indicates the occurrence of cryptic species in these regions, which cannot yet be identified either with just chromosomal or morphological analyzes.
Keywords: Ancistrini; Catfish; distance tree; mitochondrial DNA; taxonomy